CONVERSATIONAL IMPLICATURE ANALYSIS IN SPOKEN QUOTATION WORDS USED BY THE MAIN CHARACTERS OF 5CM NOVEL - IDAMANINGATI, TITIS (Jurnal Ilmiah Mahasiswa FIB, 2013)
In order to communicate well with the readers, novel authors try to direct  the readers to understand the general life stories of the novel. They sometimes  insert some quotation or citation to complete  or support their works. In line with that, Grice (2002) notices when people communicate in daily conversations, they often make their literal expression implied. Thus, the researcher found that a case of creating implicature by flouting maxims in spoken quotation words is used by the main characters in 5CM novel. This research was conducted to answer two research problems ; (1) What are the types of flouted maxim found in spoken quotation  used by the main characters of 5CM novel?; (2) What are the implied meanings of flouted maxims found  in spoken quotation used by the main characters of 5CM  novel?. Those research problems had purposes to find out the types of flouting maxims and to describe the implied meanings of flouted maxims found  in spoken quotation used by the main characters of  5CM  novel.A descriptive qualitative method is used because the data are in the form of words which are explained descriptively and briefly by using Grice’s theory of implicature. The data are the main characters’ spoken quotation words that consist of twenty quotations. It was taken from Doni Dhirgantara’s 5CM novel.After the data were identified and analyzed, the reseracher finds that there are flouted maxim of quality, quantity, relevance, and manner. In this novel, the quotation which flout maxim of quality is absurd. Meanwhile, the contribution of maxim of quantity is overinformative. Flouting maxim of relevance happens when the speaker makes unrelated quotation with the topic being discussed. The flouting maxim of manner occurs when the speaker says too long winded that is ambigous. Then, the researcher also finds that the implied meanings behind flouted maxim are convincing something, expressing feeling and conditions, clarifying something and hiding feeling.Finally, it is suggested that this research will be one of additional references in the filed of Pragmatics. In addition, the next future researchers can study implicature more complete by using different subject and theory.Keywords: conversational implicature , flouting maxims, quotation words.